The Effect Of Pm2.5 Dust Exposure On Mda And 8-Ohdg Urine as an Oxidative Stress Indication Of Brick Workers in Mojokerto District, 2024 - Atikah, Atikah; Keman, Soedjajadi; A. Mirasa, Yudied (Blantika: Multidisciplinary Journal, 2024)
Exposure to PM2.5 dust could enter the human body through inhalation and have a negative impact on health through the mechanism of the formation of reactive oxygen species (ROS) in the respiratory tract, where the remaining ROS could burn cell nuclei and produce a byproduct in the form of malondialdehyde (MDA).  In addition, oxygen radicals that could enter cells could burn DNA and produce 8-hydroxy-2'-deoxyguanosine (8-OHdG). High levels of MDA and 8-OHdG in the body reflect high levels of oxidative stress. Analyze sis influence on pap a ran PM 2.5 was an indication of oxidative stress through examination of urine MDA and 8-OHdG levels in brick-making workers in Mojokerto. Regency This type of research was observational and analytical, with a cross-sectional approach. There was an influence of exposure to PM 2.5 dust particles on MDA and 8-OHdG levels. MDA and 8-OHdG levels in the urine of workers at exposed locations were higher compared to workers at unexposed locations.  The oxidative stress of workers in exposed locations was higher than that of workers in unexposed locations.